α1-Adrenergic Receptors in Neurotransmission, Synaptic Plasticity, and Cognition - Perez, Dianne M. (Frontiers in Pharmacology, 2020)
Alpha1-adrenergic receptors are G-Protein Coupled Receptors that are involved in neurotransmission and regulate the sympathetic nervous system through binding and activating the neurotransmitter, norepinephrine, and the neurohormone, epinephrine. There are three 1-adrenergic receptor subtypes (alpha1A, alpha1B, alpha1D) that are known to play various roles in neurotransmission and cognition. They are related to two other adrenergic receptor families that also bind norepinephrine and epinephrine, the beta- and alpha2-, each with three subtypes (beta1, beta2, beta3, alpha2A, alpha2B, alpha2C). Previous studies assessing the roles of alpha1-adrenergic receptors in neurotransmission and cognition have been inconsistent. This was due to the use of poorly-selective ligands and many of these studies were published before the characterization of the cloned receptor subtypes and the subsequent development of animal models. With the availability of more-selective ligands and the development of animal models, a clearer picture of their role in cognition and neurotransmission can be assessed. In this review, we highlight the significant role that the alpha1-adrenergic receptor plays in regulating synaptic efficacy, both short and long-term synaptic plasticity, and its regulation of different types of memory. We will also present evidence that the alpha1-adrenergic receptors, and particularly the alpha1A-adrenergic receptor subtype, are a potentially good target to treat a wide variety of neurological conditions with diminished cognition.